Winnie the Pooh - Milne, A. A. (Alan Alexander), 1882-1956 (Puffin Books, 1992)
The adventures of Christopher Robin and his friends, in which Pooh Bear uses a balloon to get honey, Piglet meets a Heffalump, and Eeyore has a birthday.